희렴의 Nitric Oxide 유리를 통한 평활근세포에서의 Apoptosis유도 - 전수영; 신동훈; 손창우; 신흥묵; Jun Soo Young; Shin Dong Hoon; Son Chang Woo; Shin Heung Mook (동의생리병리학회지, 2004)
Apoptosis is the ability of cells to self-destruct by the activation of an intrinsic cellular suicide program when the cells are no longer needed or when they are seriously damaged. Morphologically, apoptosis is characterized by the appearance of membrane blebbing, cell shrinkage, chromatin condensation, DNA cleavage, and the fragmentation of the cell membrane-bound apoptotic bodies. Siegesbeckia glabrescens Makino (Siegesbeckiae Herba, SG) has been widely used as treatments for arthritis, and fever, as well as detoxification properties. The present studies were undertaken to evaluate if SG has an anti-apoptotic property. Cell viability was measured by XTT and tryphan blue stain. Morphological characteristic of human aortic smooth muscle cells(HASMC) were visualized with a phase-contrast microscope. SG significantly reduced HASMC, but not human umbilical vein endothelial cell(HUVEC), viability in a dose-dependent manner. Confluent untreated cells at 24hrs showed normal morphology, flat with a uniform polygonal shape. SG-treated cells (0.5㎎/㎖) at 24hrs showed apoptotic morphology. Cells became irregular with elongated lamellipodia, and exhibited condensed chromatin in nuclei with occasional endoucleation. There was an increase in the number of apoptotic cells rounding-up and being detached from the substrate. TUNEL staining of SG-treated cells showed dark-brown stains in nuclei and cytosol. Caspases are central components of the machinery responsible for apoptosis and are generally divided into two categories; the initiator caspases, which include caspases-2,-8,-9, and -10, and the effector caspases, which include caspases-3,-6, and -7. SG decreased anti-caspase-3 protein expression, which means activation of caspases-3 activity. It has been reported that there is a link between NO formation and apoptosis. NO production was accelerated by SG treatment in HASMC. L-NNA, NOS inhibitor, inhibited SG-induced apoptosis. These results, therefore, indicated that both caspases-3 and NO production are involved in apoptosis in smooth muscle cells. According to these results, SG may have a potential effect in the treatment of hypertensive atherosclerosis.